2017
DOI: 10.1021/acs.inorgchem.7b01238
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Bromide to Bromine by Ruthenium(II) Bipyridine-Type Complexes Using the Flash-Quench Technique

Abstract: Six ruthenium complexes, [Ru(bpy)] (1), [Ru(bpy)(deeb)] (2), [Ru(deeb)(dmbpy)] (3), [Ru(deeb)(bpy)] (4), [Ru(deeb)] (5), and [Ru(deeb)(bpz)] (6) (bpy: 2,2'-bipyridine; deeb: 4,4'-diethylester-2,2'-bipyridine; dmbpy: 4,4'-dimethyl-2,2'-bipyridine, bpz: 2,2'-bipyrazine), have been employed to sensitize photochemical oxidation of bromide to bromine. The oxidation potential for complexes 1-6 are 1.26, 1.36, 1.42, 1.46, 1.56, and 1.66 V vs SCE, respectively. The bimolecular rate constants for the quenching of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…Yun-Da Tsai et al have reported the photocatalytic oxidation of bromide by ruthenium polypyridyl species in acetonitrile solution. , In their early study, photooxidation of bromide was achieved with the [Ru­(deeb) 2 (dmb)] 2+* excited state. However, the second-order rate constant for bromide oxidation k = 2 × 10 6 M –1 s –1 was small, resulting in inefficient excited-state quenching attributed to a small thermodynamic driving force.…”
Section: Halide Photoredox Chemistry With Metal-to-ligand Charge-tran...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yun-Da Tsai et al have reported the photocatalytic oxidation of bromide by ruthenium polypyridyl species in acetonitrile solution. , In their early study, photooxidation of bromide was achieved with the [Ru­(deeb) 2 (dmb)] 2+* excited state. However, the second-order rate constant for bromide oxidation k = 2 × 10 6 M –1 s –1 was small, resulting in inefficient excited-state quenching attributed to a small thermodynamic driving force.…”
Section: Halide Photoredox Chemistry With Metal-to-ligand Charge-tran...mentioning
confidence: 99%
“…In a follow-up study of these consecutive bimolecular reactions, a series of six different ruthenium complexes [Ru­(bpy) 3 ] 2+ , [Ru­(bpy) 2 (deeb)] 2+ , [Ru­(deeb) 2 (dmb)] 2+ , [Ru­(deeb) 2 (bpy)] 2+ , [Ru­(deeb) 3 ] 2+ , and [Ru­(deeb) 2 (bpz)] 2+ was investigated . These complexes were evaluated for their photophysical and redox properties and were found to have Ru III/II potentials that ranged from 1.51 to 1.91 V vs NHE.…”
Section: Halide Photoredox Chemistry With Metal-to-ligand Charge-tran...mentioning
confidence: 99%
“…Excited state electron transfer reactions are central to molecular level approaches to solar energy conversion. Recently hydrohalic acid splitting has re-emerged as a promising target. Hydrobromic acid (HBr) is of particular interest in this regard, eq , as the hydrogen and bromine products are solar fuels amenable to storage in flow batteries , and fuel cells. Here we report bromide photo-oxidation sensitized to visible light with a Ru diimine complex. …”
Section: Introductionmentioning
confidence: 98%
“…Recent results in this area have shown that ruthenium tris-bipyridine dyes are competent chromophores for the oxidation of bromine in nonaqueous media. [26][27][28] The core-shell electrode configuration was used here in anticipation of the slower ET rate between RuP 3+ (formed following excited state injection, E1/2 = 1.26 V versus NHE) and Br -(E1/2 = 1.05-1.09 V versus NHE). [29] The longer charge separation lifetimes provided by the core-shell electrodes have resulted in enhanced photocurrent efficiencies which in some cases are a >10-fold enhancement over traditional TiO2 electrodes.…”
mentioning
confidence: 99%